Digitalisasi Tata Kelola Pesantren Al Ajwa Al Islamy Melalui Pelatihan dan Pendampingan Goponpes-Digital Menggunakan Google Workspace dan Sistem Informasi Akuntansi - Hery Dwi Yulianto; Nia Karniawati; Ony Widilestariningtyas (Jurnal Impresi Indonesia, 2025)
Pesantren as traditional Islamic educational institutions face challenges in transparent and accountable administrative and financial governance in the digital era. The Al Ajwa Al Islamy Islamic Boarding School with 420 students and 17 managers still relies on manual recording that is prone to errors, physical archives that are prone to loss, and digital gaps between generations of managers. This study aims to analyze the effectiveness of the implementation of digitization of pesantren governance through the GOPONPES-DIGITAL program using Google Workspace and Google Sheets-based Accounting Information System. The implementation method uses a participatory approach with stages of socialization, Google Workspace training, SIA implementation, cross-generational mentoring, and pretest-posttest evaluation. Participants involved pesantren managers, teachers, senior students, and UNIKOM students as companions. The training includes Google Docs, Sheets, Drive, Gmail, and Calendar, followed by the implementation of financial recording templates and digitization of administrative records. The results of the implementation show a significant increase in managers' digital literacy from basic to intermediate levels based on pretest-posttest evaluation. Financial records become more efficient, transparent, and real-time with minimal error rates. Structured digital filing systems reduce the risk of losing important documents. Cross-generational mentoring successfully bridges the digital divide, with the formation of an internal digital team that is sustainable. The monthly reporting process can be generated automatically with high accuracy. The GOPONPES-DIGITAL program has proven to be effective in improving pesantren governance through adaptive digital transformation without abandoning traditional values. This model has the potential to be replicated to other Islamic boarding schools as a solution to digitize educational institutions based on religious communities.